Knowledge and Attitudes of Environmental and Occupational Health Engineering Students towards the Benefits and Risks of Nanotechnology - Mohammad Javad ASSARI; Ali Mohammad ABBASI; Taleb ASKARIPOOR; Elaheh KAZEMI (Shahid Sadoughi University of Medical Sciences, 2017)
Introduction: Nanotechnology as a key technology in the 21st century refers to the science of manipulating molecules and atoms in size range of 1 to 100 nanometers. Given the importance of investment in research and development, promoting knowledge and attitude of students can have a positive effect on expanding the scope and use of these emerging technologies. Methods: In this descriptive analytical study, the knowledge and attitudes of 130 students towards the benefits and risks of nanotechnology were investigated through a questionnaire. The participants were studying occupational and environmental health engineering in Hamadan, Ilam, and Semnan Universities of Medical Sciences. Results: The mean score of students' knowledge was 16.08 ± 1.61. A significant difference was observed between the mean scores of knowledge in undergraduate and graduate students (P= 0.001). However, no significant deference was observed in the mean score of knowledge between women and men, different age groups, and the year of entrance to university. Using linear regression equation and by considering knowledge level as a dependent variable, it was indicated that age and educational level were significantly related to the state of knowledge. Conclusion: The results showed that most students did not have an acceptable level of knowledge about nanotechnology. Considering the benefits and risks of this technology, students have a positive attitude to develop use of nanotechnology in Iran.